1967
DOI: 10.1785/bssa0570030341
|View full text |Cite
|
Sign up to set email alerts
|

Model and theoretical seismicity

Abstract: A laboratory and a numerical model have been constructed to explore the role of friction along a fault as a factor in the earthquake mechanism. The laboratory model demonstrates that small shocks are necessary to the loading of potential energy into the focal structure; a large part, but not all, of the stored potential energy is later released in a major shock, at the end of a period of loading energy into the system. By the introduction of viscosity into the numerical model, aftershocks take place following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
415
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,353 publications
(425 citation statements)
references
References 6 publications
7
415
2
1
Order By: Relevance
“…In this scenario, stress interaction between different patches of the fault, that is, the stress contribution at location Σ resulting from an earthquake located outside Σ, can be modeled analytically using the slider block concept. Here the 2D face of the large‐scale fault consists of many smaller fault patches, which may slip independently but are mechanically coupled to their neighbors (Bak & Tang, 1989; Burridge & Knopoff, 1967). The stability of a fault patch is controlled by Equation 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, stress interaction between different patches of the fault, that is, the stress contribution at location Σ resulting from an earthquake located outside Σ, can be modeled analytically using the slider block concept. Here the 2D face of the large‐scale fault consists of many smaller fault patches, which may slip independently but are mechanically coupled to their neighbors (Bak & Tang, 1989; Burridge & Knopoff, 1967). The stability of a fault patch is controlled by Equation 1.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the slider‐block concept (Burridge & Knopoff, 1967), I provide a framework for inferring the spatio‐temporal evolution of pore pressure changes for the specific scenario of induced seismicity occurring on a single, larger scale fault. Previous studies demonstrate that this scenario applies to the seismicity induced during hydraulic stimulations of a geothermal reservoir in the Cooper Basin, Australia (Baisch et al, 2006, 2009, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been applied to a variety of fields, such as condensed matter physics [ 22 , 23 , 24 ], geophysics [ 6 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], civil engineering [ 35 , 36 , 37 , 38 ], climatology [ 39 , 40 , 41 , 42 ], and biomedical engineering [ 43 , 44 ]. Within the concept of NTA, it has been shown that the variance of natural time may be considered as an order parameter for seismicity [ 3 , 45 , 46 , 47 , 48 , 49 ] as well as in acoustic emission before fracture [ 28 , 50 ] or in other self-organized critical phenomena such as ricepiles [ 51 ] and avalanches in the Olami–Feder–Christensen [ 52 ] earthquake model [ 53 ] or in the Burridge–Knopoff [ 54 ] train model [ 55 ]. Especially for seismicity, the study of this order parameter by means of its variability [ 56 ] revealed [ 9 , 21 , 57 , 58 , 59 , 60 , 61 ,…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, various papers have investigated interfacial slip and its impact upon sliding. One early model that has been widely cited is the Burridge-Knopoff (BK) model (Burridge and Knopoff, 1967), which was developed to better understand the behavior of earthquakes. The BK model involves the dynamic motion of a linear array of blocks, each of which is coupled by a leaf spring to a horizontally translating support, as well as coupled to its two nearest neighbors by linear springs, with each block interacting with a stationary surface via frictional contact.…”
Section: Introductionmentioning
confidence: 99%